Information Technology, Organization, and Productivity in the Public Sector: Evidence from Police Departments - Garicano, Luis; Heaton, Paul (Journal of Labor Economics, 2010)
We examine the relationship between information technology (IT), productivity, and organization using a new panel data set of police departments that covers 1987–2003. When considered alone, increases in IT are not associated with reductions in crime rates, increases in clearance rates, or other productivity measures, and computing technology that increases reported crime actually generates the appearance of lower productivity. These results persist across various samples, specifications, and IT measures. IT investments are, however, linked to improved productivity when they are complemented with particular organizational and management practices, such as those associated with the Compstat program.